Small nuclear RNAs are encoded in the nontranscribed region of ribosomal spacer DNA. - Reichel, R (1982)
The structure of in vitro synthesized mouse small nuclear RNA transcribed by RNA polymerase I (snPI RNA) was studied by T1 RNase digestion pattern analysis. The patterns of four different snPI RNA species were different from those of the U1 and U2 RNA species. In addition, the four different snPI RNA species, ranging from 130 to 240 nucleotides in length, yielded almost identical patterns. The snPI RNA molecules hybridized to cloned mouse ribosomal DNA containing the nontranscribed spacer DNA and 45S ribosomal precursor RNA molecules did not compete with this hybridization. Southern blot analysis of fragments from the ribosomal DNA confirmed that snPI RNA species exclusively hybridized to sequences corresponding to the so-called nontranscribed ribosomal spacer region.